SCHOOL SUPERVISION TEACHER’ JOB PERFORMANCE AND STUDENTS ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN FEDERAL CAPITAL TERRITORY, ABUJA, NIGERIA - Udegbe Chigozie Charles; Nwankwo Nkechi Chinelo; Job John Edor (PT. Antis International Publisher, 2025)
The study investigated the impact of school supervision on teachers’ job performance and students’ academic performance in Public Secondary Schools in Federal Capital Territory, Abuja, Nigeria. The study adopted a descriptive survey research design. A sample of 480 respondents (30 principals, 150 teachers, and 300 students). The main instruments for data collection were Questionnaires. All instruments were structured on a four-point Likert scale ranging from Strongly Agree to Strongly Disagree (1). The instruments were subjected to content and face validity by three experts in Educational Administration and Planning from the University of Abuja. Their suggestions were incorporated to improve clarity, relevance, and adequacy of the items to the research objectives. Descriptive statistics such as frequency counts, means, and standard deviations were used to analyze responses to research questions. Pearson Product Moment Correlation (PPMC) was employed to test the hypotheses and determine the relationships among school supervision, teacher job performance, and students’ academic performance at a 0.05 level of significance. The result collected revealed that school supervision positively influence the teachers’ job performance in Public Secondary Schools in Federal Capital Territory, Abuja, Nigeria. The study also showed that school supervision influences students’ academic performance in Public Secondary Schools in Federal Capital Territory, Abuja, Nigeria. The paper recommends that the Federal Capital Territory Secondary Education Board should ensure that school supervision is conducted regularly and systematically across all public secondary schools. Supervisory activities should be used to develop targeted intervention programs aimed at improving students’ academic achievement. School administrators should use supervision reports to identify teachers’ training needs, provide capacity-building workshops, and improve teaching resources.